Methadone dose at the time of release from prison significantly influences retention in treatment: Implications from a pilot study of HIV-infected prisoners transitioning to the community in Malaysia - Wickersham, Jeffrey A.; Ahmad Zahari, Muhammad Muhsin; Azar, Marwan M.; Kamarulzaman, Adeeba; Altice, Frederick L. (Elsevier, 2013)
Objective: To evaluate the impact of methadone dose on post-release retention in treatment among HIV-infected prisoners initiating methadone maintenance treatment (MMT) within prison. Methods: Thirty HIV-infected prisoners meeting DSM-IV pre-incarceration criteria for opioid dependence were enrolled in a prison-based, pre-release MMT program in Kiang Valley, Malaysia; 3 died before release from prison leaving 27 evaluable participants. Beginning 4 months before release, standardized methadone initiation and dose escalation procedures began with 5 mg daily for the first week and 5 mg/daily increases weekly until 80 mg/day or craving was satisfied. Participants were followed for 12 months post-release at a MMT clinic within 25 kilometers of the prison. Kaplan-Meier survival analysis was used to evaluate the impact of methadone dose on post-release retention in treatment. Findings: Methadone dose >= 80 mg/day at the time of release was significantly associated with retention in treatment. After 12 months of release, only 21.4 of participants on <80 mg were retained at 12 months compared to 61.5 of those on >= 80 mg (Log Rank chi(2) = (1,26) 7.6, p < 0.01). Conclusions: Higher doses of MMT at time of release are associated with greater retention on MMT after release to the community. Important attention should be given to monitoring and optimizing MMT doses to address cravings and side effects prior to community re-entry from prisons. (C) 2013 Elsevier Ireland Ltd. All rights reserved.